Combined method of flow-reduced dump load for frequency control of an autonomous micro-hydropower in ac microgrids (2021)
Nowadays, microgrids (MGs) play a crucial role in modern power systems due to possibility of integrating renewable energies into grid-connected or islanded power systems. The Load Frequency Control (LFC) is an issue of paramount importance to ensure MGs reliable and safe operation. Specifically, in AC MGs, primary frequency control of each energy source can be guaranteed in order to integrate other energy sources. This paper proposes a micro-hydro frequency control scheme, combining the control of a reduced dump load and the nozzle flow control of Pelton turbines operating in autonomous regime. Some works have reported the integration of dump load and flow control methods, but they did not reduce the dump load value and adjust the nozzle flow linearly to the power value demanded by users, causing the inefficient use of water. Simulation results were obtained in Matlab®/Simulink® using models obtained from previous research and proven by means of experimental studies. The simulation of the proposed scheme shows that the frequency control in this plant is done in correspondence with the Cuban NC62-04 norm of power energy quality. In addition, it is possible to increase energy efficiency by reducing the value of the resistive dump load by up to 7.5% in a case study. The validation result shows a 60% reduction of overshoot and settling time of frequency temporal behavior of the autonomous micro-hydro.